MINDBOT: DESIGN AND IMPLEMENTATION OF A MIND-CONTROLLED EDUCATIONAL ROBOT TOY FOR DISABLED CHILDREN - Khalid, Sibar J.; Ali , Ismael A. (Science Journal of University of Zakho, 2024)
The mindBot robot is a new educational robot toy that can be controlled by brain signals and voice commands. It was evaluated with children with disabilities as well as healthy children as the potential users. The most significant challenge was the size of the used Emotiv Insight electroencephalogram headset when adjusting it on the children’s’ heads. Despite all the challenges, the mindBot robot is a promising technology that could be fun and educational for disabled children. The 11 participants took 36 minutes to finish all tasks on average. This includes the time they spent setting up the robot for the first time, putting on the headset, learning how to use the robot, and using the main educational features. The System Usability Scale usability score for the robot is 71.13, which is considered to be the score of good. The future stages of improving the mindBot includes adding more mobility capabilities and adding the feature of educational assessment.
Keywords: mindBot; Brain Computer Interface; Robotics; Robot Toy; EEG headset; Emotiv Insight; Raspberry Pi; Human Robot Interaction